Influences of compressive stress and aging on dielectric properties of sodium bismuth titanate ceramics - Sareein T. (2014)
The influences of compressive stress and aging on dielectric properties of undoped and Fe-doped sodium bismuth titanate (NBT) ceramics were investigated. The dielectric properties were decreased significantly with the compressive stress applied parallel to the electric field direction, while the changes were reversed with the stress applied perpendicularly. In addition, lower changes of the dielectric properties with stress were observed in Fe-NBT ceramics, likely caused by an enhanced relaxor characteristic with the acceptor doping, which also reduced the aging rate in the ceramics. Finally, the aging behavior of the NBT and Fe-NBT ceramics followed the slightly stretched exponential law, and the aging rate in both ceramics was found to decrease with frequency, a result of the pinning of the polarization components. These observations clearly confirmed the role of the acceptor dopant in enhancing the relaxor ferroelectric characteristics in the NBT-based ceramics. © 2009 Elsevier B.V. All rights reserved.